Samobójstwo, wypadek, a może morderstwo? Wokół śmierci Jerzego Zawieyskiego (1969 rok) - Pleskot, Patryk (Pamięć i Sprawiedliwość, 2014)
The mysterious death of Jerzy Zawieyski, a playwright, editor and Catholic-political activist, has not been fully explained. Although according to the most plausible theory Zawieyski died on 18 June 1969 in an accident, a suicide cannot be ruled out, while there are some people who read the participation of third parties or even political murder elements into the case. The article will not burst the bubble of doubts. Even though the author managed to reach some sources which had not been utilized before, the considerations presented below will recall the tragic death of Zawieyski, underline the lack of integrity in the actions of the former authorities and point to interpretational difficulties rather than propose a final answer to the riddle.